Design of Rice Dryer Automation System Using Fuzzy MIMO Method - Gamma Aditya Rahardi; Widjonarko Widjonarko; Satryo Budi Utomo Utomo (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2022)
Rice is one of the most important cultivated plants in human civilization. One of the most important post-harvest processes is drying. Therefore, we need a drying process with an artificial heat source that can be adjusted to achieve constant heat according to the temperature characteristics of the rice. By applying the Fuzzy-MIMO control system, rice drying is expected to work quickly without damaging the rice foam. Fuzzy-MIMO system is translated into a rule based on the fuzzy algorithm that has been created. The fuzzy-MIMO method used is the Sugeno method with input temperature errors and humidity errors and outputs in the form of heat and wind gusts. The temperature sensor used has an error factor of 3.61%. The expected control system is a heating system and a motor to regulate the wind gusts in the drying chamber. The total drying time produced is 240 seconds with a moisture content of 15.2%. Drying time is influenced by the initial moisture content of rice.